Unjuk kerja kolektor surya pelat datar dengan variasi ketinggian sirip (L/Lf) pada pelat absorber - -, Amrizal (Jurnal Energi Dan Manufaktur; Vol 1, No.2 Desember 2006, 2012)
The main objective of this research is to know how far the influence of the addition of continuous longitudinal fins on enhancing the performance of solar collector. The addition of continuous longitudinal fins to the bottom side of the absorber plate using fin ratio (L/Lf) =2; 1.3; 1 increases the heat transfer and pressure drop. Optimization is done to get the optimum heat transfer and low difference of pressure drop. By experimental study, this present research shows that fin ratio ( L/Lf ) =1 is the optimum condition which give the average efficiency of 53 % and pressure drop of 2,97 N/m2. Comparing this result with fin ratio (L/Lf) =2 and 1.3 we can see the pressure drop has not increased significantly from 2.97 to 3.3 N/m2.
Keywords: fins, solar collector, heat transfer, pressure drop, optimization